Probe Position Errors Corrected Near-Field – Far-Field Transformation with Spherical Scanning - D’Agostino, F.; Ferrara, F.; Gennarelli, C.; Guerriero, R.; Migliozzi , M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Two effective approaches to correct known positioning errors in a near-field – far-field (NF–FF) transformation with spherical scan for electrically long antennas are proposed and validated numerically and experimentally. They rely on a nonredundant sampling representation of the voltage acquired by the probe, obtained by assuming that the antenna under test is enclosed in a cylinder ended in two half-spheres. The former approach exploits the singular value decomposition method, to retrieve the NF data at the points fixed by the sampling representation from the acquired irregularly spaced ones, and can be used when the nonuniformly spaced samples lie on nonuniform parallels. The latter employs an iterative technique, which can be adopted even if such a hypothesis is not satisfied, but requires the existence of a one-to-one correspondence associating at each uniform sampling point, the nearest nonuniform one. Once the uniform samples have been recovered, the NF data needed by the classical spherical NF–FF transformation are efficiently evaluated via an optimal sampling interpolation algorithm.